Kolory poezji (Na przykładzie poezji lirycznej Konstantego Ildefonsa Gałczyńskiego) - Rydz, Agnieszka (Przestrzenie Teorii, 2016)
The article presents the category of colour in modern Polish poetry, and based on an interpretation of Ewa Górecka’s book, Konstatnego Ildefonsa Gałczyńskiego gry barwą z wyobraźnią i kulturą [Colours as Konstanty Ildefons Gałczyński’s Play with Imagination and Culture]. The colour palette in Gałczyński’s poetry includes golden, silver, green, blue, red and black. Culture was an inspiration for the poet, but he didn’t avoid entering into dialogue with it, establishing the meanings of colours in his writing. The colours present in Gałczyński’s lyric poetry also indicate the changes in his poetic language. The way in which the poet uses them in his early works differs from their use in those created after 1945.